Transient Abnormal Myelopoiesis in Down Syndrome - Ayesha Majeed; Natasha Ali (Indian Journal of Neonatal Medicine and Research, 2017)
We report peripheral blood film and cytogenetic results of a five day old neonate who presented with history of high grade fever, vomiting and jaundice. Peripheral blood film showed presence of 30% blast cells which were large in size having abundant granular cytoplasm. Karyotyping results revealed presence of trisomy 21. She was diagnosed as a case of Down syndrome with congenital leukemia. Approximately 10% of such cases present as Transient Abnormal Myelopoiesis. Persistence of blast cells beyond six months is an indication for treatment. As the diagnosis was made retrospectively, this case highlights the importance of peripheral smear review which showed presence of abnormal cells prompting for further investigations.